TRANSFORMASI SUPERVISI AKADEMIK BERBASIS SEKOLAH TAHFIDZ DAN IMPLIKASINYA TERHADAP PENINGKATAN PRAKTIK REFLEKTIF TRANSENDENSI GURU - Fatimah, Hana; Suranti, Popi; Prayitno, Harun Joko; Sari, Dhany Efita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Contemporary educational reforms require academic supervision practices that extend beyond technical aspects of teaching and learning to incorporate values and spirituality into teachers’ professional development, particularly in Islamic educational settings. This study aims to describe the transformation of academic supervision at MI Muhammadiyah Tahfidzul Qur'an Matesih, analyze the principal’s strategies in fostering teachers’ transcendental reflective practices, and examine their implications for strengthening teacher professionalism. This research employed a qualitative approach with a single-case study design. To ensure data credibility, source triangulation was conducted by comparing data obtained from interviews, direct observations, and document analysis. The findings indicate that the transformation of academic supervision occurred through three major shifts: from incidental to scheduled supervision, from general pedagogical instruments to the integration of spiritual dimensions, and from one-way feedback to two-way reflective dialogue. The principal implemented several strategies, including weekly reflective journals, lesson study activities through professional learning communities, and the integration of Qur’anic tadabbur into reflective practices. Spiritual reinforcement was further supported through the implementation of mutaba’ah yaumiyyah to monitor teachers’ daily worship practices and mutaba’ah tahfidz to supervise and guide their Qur’anic memorization. These practices functioned as continuous reflective tools that fostered teachers’ transcendental awareness of their professional responsibilities as a form of spiritual accountability and devotion to God. The limitation of this study lies in its single-case design, which may limit the broader generalizability of the findings.